Analysis of the Use of Fine Filters on Lubricating Oil Content With Contaminant Tests in Diesel Engines - Kamal, Mustopa; Hermawan, Ade; Daging, I Ketut; Binardi, Teguh; Syam, M Yusuf; Muditha, Dewa Made (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Lubricating oil is a critical component in the operation of diesel engines, functioning to reduce wear and dissipate heat generated by friction in moving engine components. Compared to gasoline engines, diesel engines produce higher levels of carbon during combustion, necessitating the use of lubricating oil filters to remove combustion residues. Additionally, fine filters are employed to minimize contaminants present in the lubricating oil. This study aims to analyze the contaminant levels in different states of lubricating oil: new, unused oil; oil used for 500 hours without a fine filter; oil used for 500 hours with a CJC fine filter; and oil used for 1,336.5 hours with a CJC fine filter. The testing methods employed were ASTM D5185-18 and ASTM E2412-10, with all analyses conducted at the PT Petrolab Services Laboratory. The results demonstrate that the use of a CJC fine filter significantly reduces contaminants, with sodium levels at 1 ppm, silicon levels at 7 ppm, and Fuel Dilution, Water Content, and Glycol levels consistently at 0%.